A Cultural Odyssey : focus on Norwegian Art. - Butenschon, Peter; Christie, Inger Lise; Haddal, Per; Jerman, Gunnar; Johnson, Geir; Kofoed, Holger; Langslet, Lars Roar; Opstad, Jan-Lauritz; Pedersen, Jostein; Rossiné, Hans; Thiis-Evensen, Thomas; Tschudi-Madsen, Stephan (Oslo : Index Publishing A/S, 1997)
A Cultural Odyssey gives readers an overview of the arts in Norway from the ancient rock carvings to the wide spectrum of contemporary art. Norwegian painting, literature, theatre, film, music, architecture, folk art, handicrafts and design are each presented in their own individual chapture : Romanticism and Realism, It all started in Iceland, More than Ibsen, From Tempest to Tranquillity, New Musical Horizons, Arctic Melancholy, Shaped by Wood and Landscape, Pine - A Pillar of Life, Art for Living, Fantasy and Tradition, Norwegian Design. The text and illustrations in this work demonstrate how the colours and contrasts of Norway's natural surroundings have inspired the country's artists. Nature has been the guiding force behind the arts in Norway. Painters, writers, composers and architects have been inspired by the magnificence of the landscape. Its light is mirrored in the paintings of Norwegian masters, its climate sets the stage for the works of Henrik Ibsen, its power is echoed in the melody of music and its vistas are reflected in the discerning eye of the film photographer.
Munch, Edvard ; Ryggen, Hannah ; Aurdal, Synnove Anker ; Dahl, Johan C. ; Sohlberg, Harald ; Backer, Harriet ; Krohg, Christian ; Weidemann, Jakob ; Nordrum, Odd ; Widerberg, Frans ; Opdahl, Ornulf ; Rose, Knut ; Jenssen, Olav Christopher ; Torriset, Kjell ; Vikhagen, Havard ; Vigeland, Gustav ; Ibsen, Henrik ; Garborg, Arne ; Motzfeldt, Benny ; Vigeland, Tone ; Eliassen, Lillian ; Flor, Elinor ; Jessen, Gro ; Kvasbo, Torbjorn ; Verde, Johan
Engels
boek
Keywords: Noorwegen